Methimazole-induced congenital hypothyroidism affects gonocytes differentiation and arrests meiosis: role of Sertoli cells - Gómez-Zúñiga, Andrea; Landero-Huerta, Daniel Adrián; Rojas-Castañeda, Julio César; Sánchez-Huerta, Karla; Contreras-García, Itzel Jatziri; Reynoso-Robles, Rafael; Arteaga-Silva, Marcela; Vigueras-Villaseñor, Rosa María (Frontiers in Cell and Developmental Biology, 2024)
BackgroundCongenital hypothyroidism (CH) is a pathology that affects various organs, including the testicles. The mechanisms by which this condition alters fertility is unknown. This study aimed at determining if experimental CH affects gonocyte differentiation and arrests meiosis; and the possible role of the Sertoli cell (SC) in this condition.Material and MethodsTwo groups of rats consisting of Control group and Methimazole (MMI) induced CH rats were formed. The induction of CH was achieved by the administration of MMI starting on day 16 postcoitum and continued until euthanized. Euthanasia was performed at 5, 8, 10, 16 and 64 days of age. Following this, the testicular tissue of each animal was extracted and processed for histopathological and ultrastructural analysis. In addition, the tissue was used for the determination of proteins and their transcriptions, events which are characteristics of gonocyte differentiation. The SC functionality proteins was determined immunohistochemically, while sperm parameters of the cauda epididymis were verified.ResultsCH caused a delay in the gonocyte differentiation, and arrested meiosis and spermiogenesis. These events had long-term repercussions on the quality of the seminiferous epithelium. The results show that CH induces alterations in the functional state of SCs that may have led to the deficiency in the synthesis and/or in the release of molecules necessary for gonocyte differentiation; as well as disorders in the process of meiosis that resulted in sperm absence.ConclusionThese results suggest that CH affects gonocyte differentiation and arrests meiosis, possibly through altering the functional status of SCs.